Canarypox virus expressing infectious bursal disease VP2 protein as immunogen for chickens - Zanetti, Flavia Adriana (2014)
Canarypox viruses (CNPV) carrying the coding sequence of VP2 protein from infectious bursal disease virus (IBDV) were obtained. These viruses were able to express VP2 protein in vitro and to induce IBDV-neutralizing antibodies when inoculated in specific pathogen-free chickens demonstrating that CNPV platform is usefulness to develop immunogens for chickens.